The Improving Grade V Students' Learning Outcomes in Fraction Multiplication through the Student Teams Achievement Divisions (STAD) Learning Model. - Aqilah Husnul Khuluqiyyah; M. Farhan Zaky; Alya Aulia Faiza; Siti Maghfiroh; Badhar Satria Pratama (Journal of Action Research in Education, 2026)
This study aimed to improve fifth-grade students' mathematics learning outcomes on fraction multiplication through the Student Teams Achievement Division (STAD) cooperative learning model at UPTD SDN Socah 1. This classroom action research was conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 34 fifth-grade students. Data were collected through learning outcome tests, classroom observation, interview, and documentation. The results showed that students' learning outcomes improved from Cycle I to Cycle II. In Cycle I, the average score was 48.82 with a mastery percentage of 17.65%. After improvements in guidance, group management, learning media, and concept reinforcement were applied in Cycle II, the average score increased to 80 with a mastery percentage of 85.29%. These findings indicate that the STAD cooperative learning model can improve students' understanding, participation, collaboration, and learning outcomes in fraction multiplication. Therefore, STAD is effective as an alternative instructional model for improving mathematics learning outcomes in elementary school.